The structured RePsychling of talent: Talent transfer - Rea, T.; Lavallee, D. (Routledge handbook of talent identification and development in sport, 2017)
In sport, significant resources are dedicated to the development of large groups of athletes in the hope of producing elite performers. It has been estimated that the expenditure required to achieve an Olympic gold medal is about A$37 million and A$8 million per medal (Hogan & Norton, 2000). However, many identified athletes fail to reach their potential, which raises questions regarding the most effective and efficient use of resources to ensure optimal talent development, retention and ultimately successful athletic performance. If it were possible to minimize type II errors (e.g., those athletes who are already identified by the governing body and in the talent pathway but who do not successfully transition to senior level), this would enable sporting bodies and agencies to focus expenditure on developing a smaller number of athletes and offer more focused coaching and resources in their quest for elite performance. For more than a generation, sporting bodies, to get ahead of other respective countries and win medals on the World stage, have unwittingly called for a new capacity of talent. This talent would have the ability not just to demonstrate certain characteristics needed to perform with distinction, they would also be able to step outside the specific demands of one sport to validate their own capabilities to more steadfast characteristics needed to transfer their `talent` to another domain. The use of talent transfer is becoming increasingly common within high performance sport to help support medal-winning potential (Vaeyans, Giillich, Warr, & Phillippaerts, 2009). For example, China moved Chen Zhong from basketball to taekwondo as early as 1995 and within five years she had been selected for the national team. Zhong went on to win gold at the 2000 Olympics where taekwondo made its debut as an Olympic sport. A high-profile talent transfer in the UK was Rebecca Romero who first won silver for Britain rowing the quadruple scull at the Athens Games in 2004 and then took up cycling in 2006, winning two golds for Great Britain at the 2008 Beijing Olympics. Prevalent initiatives such as UK Sport/English Institute of Sports`Tall and Talented (2012), the Australian Institute of Sports` Second Chance and Sports Draft programmes, the Canadian Sport Institute`s Podium Search (including Row to Podium and Pedal to the Medal) and Germany`s Row4Tokyo and Zero to Hero, are indicative of the investment given to sporting bodies with the intention of creating as many chances as possible of medalling within targeted sports for future Olympic games. Collins, Collins, MacNamara and Jones (2014) analysed data from the 2010 and 2012 Olympic teams and found that from Australia, Canada, GB and USA, 174 (7.5%) athletes were identified as resulting from talent transfer. Furthermore, Collins et al. (2014) noted that Australia and the UK, who have made significant investments in their formal talent transfer initiatives, converted 8% of their Olympic athletes as transfers. These statistics suggest the notion of talent transfer may be worthwhile for sporting bodies hoping to maximize identification and development of sporting talent.